MANAJEMEN PRODUKSI CHANNEL YOUTUBE SINAU HURIP DALAM MENGEMAS KONTEN EMPATI PENANGANAN ODGJ JALANAN - Kusumawardani, Herlin Ade; Aji, Gilang Gusti (Universitas Negeri Surabaya, 2024)
Social media is developing very rapidly from year to year. Almost all people use social media to get sources of information, education, entertainment, and so on. YouTube is one of the video sharing social media that is popular among the public because it is easy to access videos and has various benefits. The aim of this research is to find out how the production management of the Sinau Hurip YouTube channel is in packaging empathetic content for people with mental disorders on the streets so that they are able to send 250 people with mental disorders back to their families. The theoretical basis used is based on from Eli M Noam which contains risk reduction techniques, product development factors, and organizational structure factors. This research uses a qualitative descriptive method. The results of this research are to find out how the Sinau Hurip YouTube channel manages humanistic, empathetic content, does not offend other parties, collaborates and builds good relationships with all parties.